2009
DOI: 10.1515/jpem.2009.22.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Auxological Evaluation and Determinants of Growth Failure at the Time of Adoption in Eastern European Adoptees

Abstract: We recommend that IAs undergo screening upon US arrival to identify risk factors for poor growth, particularly evidence of LBW and fetal alcohol exposure. Catch-up growth should be monitored in all children following adoption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 18 publications
6
35
1
Order By: Relevance
“…By adoptive parents’ report, all the institutions where the children were adopted were reported to have a poor adult-to-child ratio. The IA group had impairment of height and head size similar to that seen in previous studies (13, 14). Interestingly, we found that USN children did not demonstrate impairment of height or HC.…”
Section: Discussionsupporting
confidence: 86%
“…By adoptive parents’ report, all the institutions where the children were adopted were reported to have a poor adult-to-child ratio. The IA group had impairment of height and head size similar to that seen in previous studies (13, 14). Interestingly, we found that USN children did not demonstrate impairment of height or HC.…”
Section: Discussionsupporting
confidence: 86%
“…Thirty-four articles (representing 33 studies) contained relevant data and were selected for data extraction. A schematic diagram of the search strategy is depicted in Fig 1. Data on the prevalence of FAS and/or FASD in child-care systems were available from only 8 countries, as follows: Brazil (1 study 40 ), Chile (2 studies 41,42 ) Canada (3 studies 4,43,44 ), Israel (1 study 45 ), Russia (10 studies 11,46-55 ), Spain (1 study 56 ), Sweden (3 studies [57][58][59] ), and the United States (USA; 11 studies [60][61][62][63][64][65][66][67][68][69][70] ). One study reported on the prevalence of FAS among preadoption children from Eastern Europe (Romania, Ukraine, Moldova).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Of the studies that used an ACA approach (ie, those studies that used ACA solely, as well as those that used a mixed-methods approach), 10 studies [40][41][42][49][50][51]62,64,[69][70][71] did not report the system used for diagnosing FAS and/or FASD. Of those studies that did report the diagnostic system used, 7 studies 44,54-56,59,60,66 used the 4-Digit Diagnostic Code, 24 2 studies 48,58 used the IOM diagnostic criteria, 23 2 studies 47,68 used the CDC FAS Guidelines, 15 1 study 46 used the FASD Study Group criteria, 17 and 1 study 63 used the Smith' s Recognizable Patterns of Human Malformations.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…We and others have previously documented significant physical growth delays in up to 34% of international adoptees from Eastern Europe, South America, and Asia [35]. Of the many hereditary, environmental, and hormonal factors that may contribute, we have previously shown that age, prenatal factors (birth weight and risk of fetal alcohol syndrome), and growth factors (Insulin-like Growth Factor Binding Protein-3, IGFBP-3) are independently associated with the degree of growth delay in adoptees upon arrival into the US [4]. …”
Section: Introductionmentioning
confidence: 99%